The coiled tubing drilling rig for mineral exploration - Soe, S.; Lagat, Christopher; Evans, Brian; Mostofi, Masood; Fox, S. (2018)
Copyright © 2018, Society of Petroleum Engineers. In November 2016 the Deep Exploration Technologies Cooperative Research Centre (DET CRC) launched the RoXplorer®, a coiled tubing (CT) drilling rig for greenfields mineral exploration, delivering a platform for low-cost, rapid, safe and environmentally-friendly drilling. The launch represented an important technical milestone in the development of CT drilling for mineral exploration and has been complemented by a series of very successful field trials in the first half of 2017 The paper presents CT technology and its application for mineral exploration drilling. The three key challenges for CT drilling in mineral exploration are coil durability, drilling hard rocks with low weighton- bit and sample fidelity. Results for mineral exploration CT-drilling field-trials in the consolidated cover rocks of South Australia and the unconsolidated cover rocks of the Murray Basin in Victoria are presented and outline how each of these challenges was overcome. The outcomes confirm the promise of this cheaper regional prospecting approach to mineral exploration drilling. The results of assay samples of the CT drilling cuttings are remarkable; the assay samples from the CT drilling at Port Augusta trial matched those of diamond drill core from an adjacent hole.